2021
DOI: 10.1108/jea-10-2020-0219
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality classroom simulations: how school leaders improve instructional leadership capacity

Abstract: PurposeThe purpose of this study was to explore the utility of a virtual reality (VR) classroom experience for improving the capacity of instructional leaders. Specifically, school leaders used VR to build their classroom observation and analysis skills to prepare to have more effective post-observation conversations with teachers. The authors provide insights from multiple data points that highlight the affordances of the virtual setting for improving classroom observation skills.Design/methodology/approachDr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In regards to the first claim, Militello et al (2021) and Cunningham et al (2022) all noted that principals' perceptions of VR are determined by how useful they believe VR is to the efficiency of school operations and how easy to use is. For example, Militello et al (2021) noted that "school leaders used VR to build their classroom observation and analysis skills to prepare to have more effective postobservation conversations with teachers" (p.286). In addition, Cunningham et al (2022) found that principals found it easier to embrace VR if they perceived VR to be user-friendly, intuitive, and requiring minimal technical expertise to implement.…”
Section: Middle School Principals' Perception Of Vrmentioning
confidence: 99%
See 2 more Smart Citations
“…In regards to the first claim, Militello et al (2021) and Cunningham et al (2022) all noted that principals' perceptions of VR are determined by how useful they believe VR is to the efficiency of school operations and how easy to use is. For example, Militello et al (2021) noted that "school leaders used VR to build their classroom observation and analysis skills to prepare to have more effective postobservation conversations with teachers" (p.286). In addition, Cunningham et al (2022) found that principals found it easier to embrace VR if they perceived VR to be user-friendly, intuitive, and requiring minimal technical expertise to implement.…”
Section: Middle School Principals' Perception Of Vrmentioning
confidence: 99%
“…In regards to the second claim, García-Vandewalle García et al ( 2022) and Militello et al (2021) found that principals who were optimistic about the potential of VR to improve student classroom engagement, academic achievement, and classroom management effectiveness were more inclined to adopt VR. This finding reflects the optimism of middle school principals' attitudes toward VR.…”
Section: Middle School Principals' Perception Of Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advancement of technology, virtual classes become much more accessible, particularly in social sciences [8]. It is increasingly important to predict the success of students in higher education institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The notion of clustering is often adopted to improve the quality of an enhancement learning program by separating students into groups. The Ada-boost genetically modified approach, often known as Ada-GA, were adopted by Militello et al [8] to enhance the performance of dividers. This approach was utilized to assess the students' risk level against a huge amount of collected data.…”
Section: Literature Reviewmentioning
confidence: 99%